2020
DOI: 10.3390/ani10030508
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Fatty Acids from Different Sources on Growth Performance, Meat Quality, Muscle Fatty Acid Deposition, and Antioxidant Capacity in Broilers

Abstract: Simple Summary:The findings in the current study reveal that dietary fish oil or a combination of linseed oil and microalgae could be effective in improving growth performance, carcass traits, muscle fatty acid deposition, and antioxidant capacity in broilers compared with traditional soybean oil in broilers.Abstract: This study aimed to investigate the efficiency of dietary fatty acids from various sources on growth performance, meat quality, muscle fatty acid deposition and antioxidant capacity in broilers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…The PUFA are the most sensitive fractions to oxidation processes and lipid oxidation in meat ( Hashemipour et al., 2013 ); this finding might be due to the protective effect of FSE as a dietary natural antioxidant on acting as electron donors to provide electrons for reduction of some unsaturated fatty acids ( Chikunya et al., 2004 ) and improving the meat quality by increasing the n-3 PUFA (ALA or EPA) levels ( Ahmed et al., 2016 ). As noted in a previous study conducted in our laboratory, C18:3n3 and C20:5n3 as n-3 PUFA in chicken meat may be beneficial for human health ( Long et al., 2018b , Long et al., 2020 ), and lower n-6/n-3 PUFA ratio also had health benefit effects for humans, mainly in protection against cardiovascular diseases ( Chikunya et al., 2004 ). However, the mechanisms by which FSE regulates fatty acid composition of the breast meat and thigh meat in broilers are still not fully understood, and therefore, further studies are still warranted to identify these positive functions ( Pan et al., 2019 ).…”
Section: Discussionsupporting
confidence: 65%
“…The PUFA are the most sensitive fractions to oxidation processes and lipid oxidation in meat ( Hashemipour et al., 2013 ); this finding might be due to the protective effect of FSE as a dietary natural antioxidant on acting as electron donors to provide electrons for reduction of some unsaturated fatty acids ( Chikunya et al., 2004 ) and improving the meat quality by increasing the n-3 PUFA (ALA or EPA) levels ( Ahmed et al., 2016 ). As noted in a previous study conducted in our laboratory, C18:3n3 and C20:5n3 as n-3 PUFA in chicken meat may be beneficial for human health ( Long et al., 2018b , Long et al., 2020 ), and lower n-6/n-3 PUFA ratio also had health benefit effects for humans, mainly in protection against cardiovascular diseases ( Chikunya et al., 2004 ). However, the mechanisms by which FSE regulates fatty acid composition of the breast meat and thigh meat in broilers are still not fully understood, and therefore, further studies are still warranted to identify these positive functions ( Pan et al., 2019 ).…”
Section: Discussionsupporting
confidence: 65%
“…The different effects of dietary oil (rich in PUFA) on poultry performance vary from the dose, type, and composition. Long et al (2020) showed that compared with the diet supplemented with soybean oil, the diets supplemented with microalgae, linseed oil, and fish oil significantly increased the ADG and reduced the FCR of broilers from d 1 to 21. Chen et al (2014) showed that dietary supplemented with 15% linseed oil significantly improved the FCR and laying rate of geese, also indicating that an appropriate portion of n-3 PUFA can improve the performance of laying geese.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have been indicated that the fatty acid composition of poultry tissues was generally a reflection of dietary fatty acids profile (Kurniawan et al, 2015; Long et al, 2020). In the current study, increasing parental dietary arachidonic acid supplementation resulted in a concomitant increase in serum arachidonic acid proportion.…”
Section: Discussionmentioning
confidence: 99%